Analisis Kemampuan Membaca Pemahaman Siswa Kelas III di MI Padangsidimpuan Angkola Julu - Siregar, Indah Amaliyah; Ikawati, Erna (Lembaga Yasin AlSys, 2025)
Reading comprehension has been extensively examined in elementary education research; however, studies that specifically explore the reading comprehension processes of third-grade students in madrasah ibtidaiyah using a qualitative approach remain limited. This study aimed to describe the reading comprehension skills of third-grade students at MI Padangsidimpuan Angkola Julu, identify variations in their proficiency levels, and uncover the obstacles they experience in understanding texts. The study employed a qualitative approach with a descriptive design, involving 21 third-grade students, of whom 8 were selected as focal subjects for in-depth analysis through purposive sampling. Data were collected using reading comprehension tests, semi-structured interviews, and observation, and were analyzed through the stages of data reduction, data display, and conclusion drawing. The findings indicate a range of reading comprehension ability from very good to low, with major difficulties observed in identifying main ideas, drawing conclusions, and articulating the moral message of the text. These results reinforce the understanding that reading comprehension is a complex and contextual cognitive process and underscore the importance of process-oriented reading instruction in madrasah ibtidaiyah to support students in developing more optimal text comprehension skills.